Donor–Acceptor Heterojunction Configurations Based on DNA–Multichromophore Arrays. Issue 33 (14th July 2015) - Nakamura, Mitsunobu; Tsuto, Koji; Jomura, Ayumi; Takada, Tadao; Yamana, Kazushige
Abstract Multichromophore arrays of bis(2‐thienyl)diketopyrrolopyrrole (DPP) and naphthalenediimide (NDI) with two ZnII‐cyclens were constructed using thymidine DNA as a scaffold through the binding of the ZnII‐cyclens with thymine bases. We demonstrate photocurrent generation in a donor–acceptor heterojunction configuration consisting of the DPP (donor) and NDI (acceptor) arrays co‐immobilized on an Au electrode. The co‐immobilized electrode exhibited good photocurrent responses because of the efficient charge separation between the DPP and NDI arrays. In contrast, an immobilized electrode consisting of randomly assembled DPP‐NDI arrays generated no photocurrent response because DPP formed ground‐state charge‐transfer complexes with NDI in the randomly assembled arrays. Therefore, our approach to generate donor–acceptor heterojunctions based on DNA–multichromophore arrays is a useful method to efficiently generate photocurrent.